Implementasi Metode Profile Matching pada Sistem Pendukung Keputusan Seleksi Penerima Bantuan Rutilahu - Lusiana, Novita; Aryanti, Utami (Ma'soem University, 2025)
The Housing Improvement Assistance Program for Uninhabitable Houses (RUTILAHU) is one of the government’s efforts to improve the quality of life of low-income communities by enhancing their housing conditions. The selection process for aid recipients in Cijagra Paseh Village has traditionally been conducted manually through field surveys and village deliberations, which may lead to subjectivity, mistargeting, and a lack of transparency in the assessment process. This study aims to develop a decision support system that assists in selecting RUTILAHU aid recipients objectively and systematically using the Profile Matching method. Additionally, the system development process adopts the Waterfall methodology, which includes structured stages of requirements analysis, system design, implementation, testing, and maintenance to ensure system reliability and quality. The Profile Matching method operates by comparing the ideal recipient profile with the actual conditions of candidates through gap calculations, weighting of core and secondary factors, and generating final scores used to determine priority rankings. The results indicate that the Profile Matching-based decision support system provides more accurate and consistent recommendations compared to manual methods, while also improving the efficiency and transparency of the selection process for village authorities. Thus, the system has the potential to serve as an effective tool in ensuring that RUTILAHU assistance is properly targeted according to the needs of the Cijagra Paseh community.